Marketing mix at JSC Trade and Tourism Au Viet - Nguyen, Thi Minh Thu (Khoa Quốc tế, ĐHQGHN, 2020)
The thesis systematizes the basic theoretical issues of marketing mix in tourism business, studies and evaluates the current situation of marketing activities at JSC Trade and Tourism Au Vietin the 2015 – 2017 period of time. The thesis utilizes research methods such as questionnaire survey method, in-depth interview method to collect marketing mix information, database in JSC Trade and Tourism Au Viet. From that point, atable of frequencies is used to process, analyze the data, and provide accurate assessments of the research problem. Lastly, the thesis recommends several solutions for the company to improve the efficiency of marketing mix implementation in the upcoming years.